Malaysia's Sustainable Future: Navigating Industry 4.0 through a Low-Carbon Agenda - Shaharudin, Muhammad Shabir; Fernando, Yudi; Gani, Anisha Banu Dawood (International Journal of Industrial Engineering, Technology & Operations Management, 2023)
The evolving technological landscape has transformed the business realm, compelling companies to navigate a dynamic environment and embrace innovation to maintain competitiveness. One of the most recent trends in this pursuit is the Industrial Revolution or Industry 4.0 (IR 4.0). Industry 4.0 has been widely discussed as a means of providing greater advantages for countries and firms. However, the shift to automation and data-driven decisions of IR 4.0 is still slow, especially in developing countries like Malaysia. Throughout the world, IR 4.0 is still in policy development, and the literature shows that IR 4.0 is still in the conceptual stage. As IR 4.0 is inevitable, countries like Malaysia must start gearing toward readiness. This must be done without impacting the environment, such as by increasing carbon emissions. In order to do that, this paper has investigated the challenges, impact, issues, enforcement and risk minimization of IR 4.0 without sacrificing low carbon performance among Malaysian firms. The review of current literature and whitepapers found that Malaysia is still creating awareness for IR 4.0, and policymakers are still developing IR 4.0. This paper has proposed future research that will gear Malaysia to establish an IR 4.0 readiness framework and provide empirical evidence from the industry.